2011
DOI: 10.1249/mss.0b013e3181fb4e00
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Sex Difference in the Age of Elite Marathon Runners?

Abstract: These data indicate that men and women physiologically peak at a similar age in marathon running performance. The sex difference in performance of elite marathon runners varied across years but has not systemically decreased or varied since the 1980s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
159
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(182 citation statements)
references
References 22 publications
18
159
4
1
Order By: Relevance
“…The age of Olympic gold medal winners in the men's 100m dash was at ~23 years between 1896 and 1980. Similar results were found for other distances as for short and middle distance running [4], half-marathon running [19], marathon running [20] and ultra-marathon running [21]. In other endurance sports disciplines such as Ironman triathlon, the age of peak swimming speed increased in the swim split across years [22].…”
Section: Introductionsupporting
confidence: 79%
“…The age of Olympic gold medal winners in the men's 100m dash was at ~23 years between 1896 and 1980. Similar results were found for other distances as for short and middle distance running [4], half-marathon running [19], marathon running [20] and ultra-marathon running [21]. In other endurance sports disciplines such as Ironman triathlon, the age of peak swimming speed increased in the swim split across years [22].…”
Section: Introductionsupporting
confidence: 79%
“…[38,83,86,88] It has been found that the age of peak performance in Ironman triathlon is around 33-34 years for both males and females [32,57] , which seems to be older than the age of peak overall performance of marathoners. [99] However, this finding observed for the Ironman Switzerland triathlon needs be confirmed for other Ironman events. For non-elite triathletes, the fastest race times are usually achieved between 25 and 44 years for both Ironman and Ultra-triathlons.…”
Section: Age-related Declines In Triathlon Performancementioning
confidence: 85%
“…Figure 1 suggests the existence of a "maturation" process for marathon performance, although this effect might be related to training (young athletes typically compete over shorter distances) rather than a biological explanation. Second, Hunter et al (2011) indicated that men and women physiologically peaked at a similar age in marathon running performance. The maximal performance of the top five runners in the World Marathon Majors Series and in the International Athletic Association Federation World Championship was obtained at~30 years of age for both sexes, while older runners (from 30 to 54 years) obtain the best race times in 100-km competitions (Knechtle et al 2012).…”
Section: Discussionmentioning
confidence: 99%